Molecular insight and mode of inhibition of α ‐Glucosidase and α ‐Amylase by Pahangensin A from Alpinia pahangensis Ridl. - Loo, Kong Yong; Leong, Kok Hoong; Yasodha Sivasothy, *; Halijah Ibrahim,; Khalijah Awang, (Wiley, 2019)
The inhibition of carbohydrate‐hydrolyzing enzymes in human digestive organs is crucial in controlling blood sugar levels, which is important in treating type 2 diabetes. In the current study, pahangensin A (1), a bis‐labdanic diterpene characterized previously in the rhizomes of Alpinia pahangensis Ridl., was identified as an active dual inhibitor for α‐amylase (IC50=114.80 μm) and α‐glucosidase (IC50=153.87 μm). This is the first report on the dual α‐amylase and α‐glucosidase inhibitory activities of a bis‐labdanic diterpene. The Lineweaver‐Burk plots of compound 1 indicate that it is a mixed‐type inhibitor with regard to both enzymes. Based on molecular docking studies, compound 1 docked in a non‐active site of both enzymes. The dual inhibitory activity of compound 1 makes it a suitable natural alternative in the treatment of type 2 diabetes.